Leader Narcissism and Employee Organizational Citizenship Behavior Directed Toward the Leader: Roles of Perceived Insider Status and Need for Self-Esteem - Wang, Huaqiang; Liu, Geng; Wang, Miao; Dong, Yue (Frontiers in Psychology, 2021)
Based on self-concept theory, the present study proposed and empirically tested the impact of leader narcissism on employee organizational citizenship behavior directed toward the leader (OCB-L), highlighting the mediating role of perceived insider status and the moderating role of need for self-esteem in this relationship. Based on an analysis of 161 two-stage matched leader-employee dyads, the hypotheses were tested and the results showed that the leader narcissism had a negative direct effect on employee OCB-L, as well as a negative indirect effect on employee OCB-L via perceived insider status. Furthermore, the need for self-esteem was found to moderate the negative effect of leader narcissism on perceived insider status as well as the mediating effect of perceived insider status between leader narcissism and employee OCB-L. The theoretical and practical implications of our research were discussed. Limitations and directions for future research were also offered.